2022
DOI: 10.1093/plphys/kiac281
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping and modeling of root hydraulic architecture reveal critical determinants of axial water transport

Abstract: Water uptake by roots is a key adaptation of plants to aerial life. Water uptake depends on root system architecture (RSA) and tissue hydraulic properties that, together, shape the root hydraulic architecture. This work investigates how the interplay between conductivities along radial (e.g. aquaporins) and axial (e.g. xylem vessels) pathways determines the water transport properties of highly branched RSAs as found in adult Arabidopsis (Arabidopsis thaliana) plants. A hydraulic model named HydroRoot was devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 75 publications
0
33
0
Order By: Relevance
“…Root system shape, structure, and plasticity impact its efficiency and condition the plant fitness in fluctuating environments [ 1 ]. The root system architecture (RSA) is dramatically affected by spatial and temporal changes in the soil environment that, in turn, will modify its water and nutrients capture efficiency [ 3 ]. These adaptive responses, including branching angles and frequencies of lateral roots, rely on growth rate modifications of the different root classes (e.g., primary, seminal, lateral, or adventitious roots).…”
Section: Introductionmentioning
confidence: 99%
“…Root system shape, structure, and plasticity impact its efficiency and condition the plant fitness in fluctuating environments [ 1 ]. The root system architecture (RSA) is dramatically affected by spatial and temporal changes in the soil environment that, in turn, will modify its water and nutrients capture efficiency [ 3 ]. These adaptive responses, including branching angles and frequencies of lateral roots, rely on growth rate modifications of the different root classes (e.g., primary, seminal, lateral, or adventitious roots).…”
Section: Introductionmentioning
confidence: 99%
“…Root system shape, structure, and plasticity impact its efficiency and condition the plant fitness in fluctuating environments (Balduzzi et al, 2017). The root system architecture (RSA) is dramatically affected by spatial and temporal changes in the soil environment that, in turn, will modify its water and nutrients capture efficiency (Boursiac et al, 2022). These adaptive responses, including branching angles and frequencies of lateral roots, rely on growth rate modifications of the different root classes (e.g., primary, seminal, lateral, or adventitious roots).…”
Section: Introductionmentioning
confidence: 99%
“…Using this method, and in combination with HydroRoot, both axial and radial conductances were obtained in a single experiment and for the same plant. With this approach, Boursiac et al (2022a ) showed that axial conductance in particular increases less with distance to the root tip than expected from classical models. They found that, in highly branched root systems, axial hydraulic conductance can be as strongly limiting as radial hydraulic conductance for water transport to shoots ( Figure 1 ).…”
mentioning
confidence: 97%
“…In this issue of Plant Physiology , Boursiac et al (2022a ) developed the hydraulic mathematical model “HydroRoot” and used it in combination with a cut-and-flow experimental procedure to investigate root hydraulic conductance of complex and highly branched root systems. In cut-and-flow experiments, entire root systems were placed into a pressure chamber, and the shoots were removed to measure pressure-induced sap flow.…”
mentioning
confidence: 99%
See 1 more Smart Citation